2012
DOI: 10.1108/09615531211255743
|View full text |Cite
|
Sign up to set email alerts
|

Mixed convection in an inclined channel with heated porous blocks

Abstract: PurposeThe purpose of this paper is to study numerically the fluid flow and heat transfer in an inclined channel provided with heated porous blocks on its lower plate.Design/methodology/approachThe Brinkman‐Forchheimer extended Darcy model with the Boussinesq approximation is adopted for the flow in the porous regions. The governing equations with the appropriate boundary conditions are solved by the control volume method. The effect of some pertinent parameters such as the buoyancy force intensity, the porous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…The paper provides comprehensive research results of thermal characteristics in metal foams. Guerroudj and Kahalerras (2012) numerically studied the effects of mixed convection in an inclined channel filled with heated porous blocks. They reported that the inclination angle of the channel plays an important role in the calculation of flow and heat transfer, hence, obtained a maximum Nusselt number at a channel angle of +90°.…”
Section: Introductionmentioning
confidence: 99%
“…The paper provides comprehensive research results of thermal characteristics in metal foams. Guerroudj and Kahalerras (2012) numerically studied the effects of mixed convection in an inclined channel filled with heated porous blocks. They reported that the inclination angle of the channel plays an important role in the calculation of flow and heat transfer, hence, obtained a maximum Nusselt number at a channel angle of +90°.…”
Section: Introductionmentioning
confidence: 99%
“…Because of an interesting thermal performance, several studies have been conducted on the thermal behavior of metal foam such as the porous block's shape and height (Guerroudj and Kahalerras, 2012), hole's density (Bhattacharya and Mahajan, 2002), air flow velocity (Byon, 2015) and particle deposition (Odabaee et al, 2013). Although most of the studies are based on active heat sinks that dissipates heat by forced convection, but air cooling heat sinks by buoyancy-induced convection are favorable from an economic point of view.…”
Section: Introductionmentioning
confidence: 99%
“…The study reveals that for large values of mixed convection parameter, the formation of boundary layer structures on the plate was observed to occur. Guerroudj and Kahalerras (2012) investigated mixed convection in an inclined channel with heated porous blocks, and their results reveal that the inclination angle of the channel can alter substantially the fluid flow and the heat transfer mechanisms, especially at high Richardson and Darcy numbers. The maximum and minimum global Nusselt numbers (Nu) are reached for α = +90 • and α = −90 • .…”
Section: Introductionmentioning
confidence: 99%